2022
DOI: 10.1128/jcm.00292-22
|View full text |Cite
|
Sign up to set email alerts
|

Effective Rapid Diagnosis of Bacterial and Fungal Bloodstream Infections by T2 Magnetic Resonance Technology in the Pediatric Population

Abstract: Children are prone to bloodstream infections (BSIs), the rapid and accurate diagnosis of which is an unmet clinical need. The T2MR technology is a direct molecular assay for identification of BSI pathogens, which can help to overcome the limits of blood culture (BC) such as diagnostic accuracy, blood volumes required, and turnaround time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
8
1
Order By: Relevance
“…The main limitations of the present study are the small sample size of our study population, the lack of a control group, and the unavailability of the T2Candida assay in our hospital at the time of the study (which could have changed the eventual number of treatment changes based on T2 results). Chance related to the small sample could also explain our 66% concordance rate between T2Bacteria and blood cultures results, which was lower than in other studies [ 16 , 18 ], although it is of note that most discordant results were negative blood cultures and positive T2Bacteria results. In this latter case, the existence of a true episode of systemic infection cannot be ruled out.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The main limitations of the present study are the small sample size of our study population, the lack of a control group, and the unavailability of the T2Candida assay in our hospital at the time of the study (which could have changed the eventual number of treatment changes based on T2 results). Chance related to the small sample could also explain our 66% concordance rate between T2Bacteria and blood cultures results, which was lower than in other studies [ 16 , 18 ], although it is of note that most discordant results were negative blood cultures and positive T2Bacteria results. In this latter case, the existence of a true episode of systemic infection cannot be ruled out.…”
Section: Discussioncontrasting
confidence: 77%
“…Since blood culture results (identification and susceptibility test) usually become available after 48–96 h from the onset of the infection [ 8 , 9 , 10 ], the use of rapid molecular tests able to anticipate the identification of causative agents and clinically relevant resistance determinants in the blood of patients with sepsis or septic shock could reduce both the time of appropriate therapy and the misuse of antibiotics (by allowing early escalation or de-escalation) [ 8 , 11 , 12 ]. The T2Bacteria and T2Resistance assays are rapid molecular tests performed on whole blood that exploit T2 Magnetic Resonance (T2MR ® ) technology (T2Biosystems, Lexington, MA, USA) [ 13 , 14 , 15 , 16 ]. This technology allows the detection of the agglomeration of superparamagnetic particles induced by the amplicons, thereby leading to the identification of different bacteria with the T2Bacteria assay ( Enterococcus faecium , Staphylococcus aureus , Klebsiella pneumoniae , Pseudomonas aeruginosa , Acinetobacter baumannii , and Escherichia coli ) and of different resistance determinants with the T2Resistance assay (bla KPC , bla OXA-48 , bla NDM , bla VIM , bla IMP , bla CTX-M-14/15 , bla CMY , bla DHA , vanA/B, mecA/C), within 3–5 h after the blood draw [ 13 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering economic factors, the cost of mNGS is considerably higher than that of the ddPCR assay. On the other hand, in the pediatric population, T2 magnetic resonance technology is expected to be an effective rapid diagnostic tool for bacterial and fungal bloodstream infections [ 16 ]. T2Bacteria and T2Candida panels have the characteristics of high sensitivity, good specificity, short time consumption, and less blood volume collection.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the rapid causative pathogen identification in the diagnosis of BSIs was prone to culture-independent, real-time polymerase chain reaction (PCR)-based, or microarrary-based methods, supplemental to conventional BC. In children, it has also been reported that current molecular approaches included a CE-marked multiplex real-time PCR diagnostic system directly from the blood, the LightCycler SeptiFast test [ 15 ], T2 magnetic resonance-based T2Candida and T2Bacteria panels [ 16 ], and plasma microbial cell-free DNA sequencing (mcfDNA-seq) [ 17 ]. Although these techniques could shorten the turnaround time to hours, there were several limitations such as medium sensitivity and specificity at low concentrations and the inability to synchronize antimicrobial susceptibility testings (ASTs).…”
Section: Introductionmentioning
confidence: 99%
“…Early identification of etiological agents and detection of antimicrobial resistance genes were essential to promptly administer a targeted therapy in such a fragile patient (Figure 2). T2Bacteria (T2 Biosystems, Lexington MA, USA) was performed for a direct-fromblood rapid identification and multiplex detection of the ESKAPE bacteria (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Escherichia coli) most commonly involved in bloodstream infections [10]. Blood cultures were performed in accordance with hospital practices and international recommendations for pediatric populations [11][12][13].…”
Section: Microbiological Investigation and Relevant Findingsmentioning
confidence: 99%